2017
DOI: 10.1063/1.4974318
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of multilayer graphene on an insulator by Ni-induced layer exchange growth of amorphous carbon

Abstract: Multilayer graphene (MLG) growth on arbitrary substrates is desired for incorporating carbon wiring and heat spreaders into electronic devices. We investigated the metal-induced layer exchange growth of a sputtered amorphous C layer using Ni as a catalyst. A MLG layer uniformly formed on a SiO2 substrate at 600 °C by layer exchange between the C and Ni layers. Raman spectroscopy and electron microscopy showed that the resulting MLG layer was highly oriented and contained relatively few defects. The present inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 38 publications
(63 reference statements)
3
52
0
Order By: Relevance
“…A layer exchange mechanism of this kind was also observed for amorphous carbon/Ni heterostructures. 23 25 Then the graphitic layers are formed at T > 500 °C ( Figure 7 c) according to results observed from XPS measurements. Finally, the graphitic phase concentration increases with the annealing temperature ( T > 700 °C), and its concentration became higher than the concentration of the disordered phase ( Figure 7 d).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…A layer exchange mechanism of this kind was also observed for amorphous carbon/Ni heterostructures. 23 25 Then the graphitic layers are formed at T > 500 °C ( Figure 7 c) according to results observed from XPS measurements. Finally, the graphitic phase concentration increases with the annealing temperature ( T > 700 °C), and its concentration became higher than the concentration of the disordered phase ( Figure 7 d).…”
Section: Resultssupporting
confidence: 64%
“…It was observed that carbon film exchanges with Ni film and graphitizes at elevated temperature. 23 25 Recent theoretical studies explained the graphitization mechanism for RTA: a-C to graphene transformation entails the metal-induced crystallization and layer exchange mechanism. Carbon dissolution in Ni was excluded.…”
Section: Introductionmentioning
confidence: 99%
“…We prepared the samples with and without a diffusion controlling Al 2 O 3 IL, which improves the crystal quality of MLG 42 . The thickness of the initial Ni layer determines the resulting MLG thickness, t , after layer exchange 41 , 42 . We varied t from 5 nm to 200 nm to investigate the effects of t on the crystal and electrical properties of the MLG.…”
Section: Resultsmentioning
confidence: 99%
“…The thickness design of the initial metal layer can easily control the resulting semiconductor layer 27 , 31 , 35 . We found the layer exchange occurs in the Co-C and Ni-C systems and fabricated a uniform 50-nm-thick MLG on an insulator 40 , 41 . Furthermore, we employed a diffusion controlling interlayer (IL) between C and Ni, which suppresses the nucleation of the MLG and results in enlargement of MLG grains 42 .…”
Section: Introductionmentioning
confidence: 91%
“…Recently, we developed metal-induced layer exchange (MILE) of a-C. 2832 In particular, MILE using Ni enabled us to synthesize uniform MLG at low temperature with a wide range of thicknesses. 29,32 Higashi et al reported the effects of an a-Ge/Au multilayer structure on the layer exchange between Au and Ge. 33,34 The grain size of the resulting Ge layer was significantly improved by using the multilayer structure.…”
Section: Introductionmentioning
confidence: 99%